"I am an engineer and therefore a radical": an interview with Lee Felsenstein, from Free Speech Movement technician to Homebrew Computer Club moderator. Issue 2 (9th June 2021) - Momméja, Julie
Abstract: The following interview delves into Lee Felsenstein's upbringing in a bohemian communist family and his path as an engineer and technologist in the San Francisco Bay Area. He discusses his role as technician of the Berkeley Free Speech Movement, co-creator of Community Memory and moderator of the Homebrew Computer Club. Felsenstein also shares his vision of "community", "convivial tools" as defined by Ivan Illich and technology as an "invisible force". He proves how his political activism has guided his technological creative process, making and sharing tools that will contribute to build convivial, open and informed communities.